Effects of pasture systems on soil compaction, aeration, and available water capacity - Silva-Parra, Amanda; Trujillo-González, Juan Manuel; Torres-Mora, Marco Aurelio (Revista de Ciencias Agrícolas, 2026)
This research is important to define which pasture systems are physically sustainable. This study assessed the effects of different pasture types on soil physical properties: degraded pastures (DP), improved pastures (IP), and silvopastoral systems (SPS) at two Llanero Piedmont locations. At location 1, the evaluated systems included an extensive DP of native grass (EDPNG), an extensive IP of Brachiaria decumbens (EIPB), and an extensive SPS of B. decumbens associated with Yopo (Anadenanthera peregrina) trees (ESPS + AP). At location 2, the evaluated systems included an extensive DP of B. decumbens (EDPB), an intensive IP of B. decumbens (IIPB), and an extensive SPS of B. decumbens associated with Acacia (Acacia mangium) trees (ESPS + A). A completely randomized factorial design (2 × 3 × 2; n=36) was used, considering location, pasture system, and soil depth (0–0.30 and 0.30–0.60 m). Soil texture, bulk density (ρb), total porosity (Tp), macroporosity and microporosity (MaP, MiP), gravimetric, volumetric (θg, θv), and available water capacity (AWC) were measured. Data were analyzed using ANOVA and Least Significant Difference (LSD) tests. At location 1, EDPNG exhibited higher ρb and lower Tp and MaP, throughout the soil profile, indicating greater soil compaction. At location 2, IP and SPS improved soil physical quality at two depths. At locations 1 and 2, θg differed significantly in DP, higher in EDPB, θv and AWC showed no significant differences. Overall, SPS at location 2 improved soil physical conditions and represent a viable strategy for enhancing soil quality in the Llanero Piedmont.